2018
DOI: 10.1242/bio.035386
|View full text |Cite
|
Sign up to set email alerts
|

A model of mucopolysaccharidosis type IIIB in pigs

Abstract: Mucopolysaccharidosis type IIIB (MPS IIIB) is a rare genetic disorder caused by loss-of-function mutations in the NAGLU gene. Pigs are an ideal large animal model for human diseases; however, a porcine model of MPS IIIB has not been reported. We have previously generated a heterozygous NAGLU-deficient (NAGLU+/-) Large White boar via a transgenic approach. Here we characterized phenotypes of the F1 offspring of this founder to establish a pig model for MPS IIIB. qRT-PCR revealed that the NAGLU expression level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Module GS (MS) was the mean value of GS of the module genes. According to the selection criteria for critical modules reported in previous studies, modules with MTRs > 0.30 and MS > 0.25 were considered as candidate modules for the following functional enrichment analysis ( Howard et al, 2017 ; Yang et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Module GS (MS) was the mean value of GS of the module genes. According to the selection criteria for critical modules reported in previous studies, modules with MTRs > 0.30 and MS > 0.25 were considered as candidate modules for the following functional enrichment analysis ( Howard et al, 2017 ; Yang et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The MPS IIIA model also demonstrated mild cerebrocortical atrophy [56]. Cerebral and cerebellar atrophy, ventriculomegaly, and abnormalities in the intracerebral capsule, parietal lobes and the thalamus have been documented in the pig model of MPS IIIB at 180 and 240 days of life, however no major alterations in density of Purkinje cells were observed [61].…”
Section: Neuronal Death In Mps IIImentioning
confidence: 99%
“…A specific model for studying the neuropathology of MPS IIIA was generated in Drosophila and showed a knockdown of SGSH limited to neurons [60]. In addition, a NAGLU heterozygous model was recently developed in large white boars and presented with common symptoms found in MPS IIIB patients, such as slow growth, early death, somatic changes and cerebral abnormalities [61]. Mouse models also show a clinical phenotype close to that seen in patients and have been used extensively in the study of MPS III.…”
Section: Animal Models Of Mps IIImentioning
confidence: 99%
“…One gene named LRRC66 was involved in diverse biological processes, including cell adhesion, cellular tra cking, and hormone-receptor interactions [28]. And other genes were mainly associated with diseases such as Mucopolysaccharidosis IIIB [29], stress-induced injury [30], oral-facial-digital syndromes [31], and breast cancer [32]. From the results, intramuscular related genes involved in fat and muscle related function were consistent with previous research, which reported that IMF is regulated through a complex pathway that interacts with muscle, fat, and connective tissue [33,34].…”
Section: Investigation Of Differential Expression Transcriptsmentioning
confidence: 99%